Smooth muscle cell and arterial aging: basic and clinical aspects. Issue 4 (5th March 2018) - Lacolley, Patrick; Regnault, Veronique; Avolio, Alberto P
Abstract: Arterial aging engages a plethora of key signalling pathways that act in concert to induce vascular smooth muscle cell (VSMC) phenotypic changes leading to vascular degeneration and extracellular matrix degradation responsible for alterations of the mechanical properties of the vascular wall. This review highlights proof-of-concept examples of components of the extracellular matrix, VSMC receptors which connect extracellular and intracellular structures, and signalling pathways regulating changes in mechanotransduction and vascular homeostasis in aging. Furthermore, it provides a new framework for understanding how VSMC stiffness and adhesion to extracellular matrix contribute to arterial stiffness and how interactions with endothelial cells, platelets, and immune cells can regulate vascular aging. The identification of the key players of VSMC changes operating in large and small-sized arteries in response to increased mechanical load may be useful to better elucidate the causes and consequences of vascular aging and associated progression of hypertension, arteriosclerosis, and atherosclerosis.